Performansi Entog (Cairina moschata) Jantan yang Diberi Ransum Berbagai Imbangan Energi/Protein pada Sistem Kandang Berbeda - Winwin Tanwiriah (Universitas Padjadjaran, 2011)
The aim of this work was to study the effect of various energy/protein ransum ratios on the performance of 108 male Muscovy ducks (Cairina moschata) of 3 weeks of age which were treated under different housing systems, i.e., cage and ranch. Research method employed a Completely Randomized Design of Factorial Nested Patterns which were energy/protein ransum (E/P) ratio (B factor) at housing systems of cage and ranch (A factor). Each treatment consisted of three ducks at two replications each. Nine E/P ratio (R) given were: R1: 2400/13; R2: 2400/15; R3: 2400/17; R4: 2600/13; R5: 2600/15; R6: 2600/17; R7:2800/13; R8: 2800/15; and R9: 2800/17. Feeding trial variable observed were: feed, energy and protein consumption, body weight gain, feed conversion ratio, carcass weight and